STATUS KEBERLANJUTAN USAHATANI AGROFORESTRY PADA LAHAN MASYARAKAT: STUDI KASUS DI KECAMATAN RANCAH, KABUPATEN CIAMIS, PROVINSI JAWA BARAT - Idin Saepudin Ruhimat (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Land use with agroforestry system has ecological, economic and social advantages, so that the sustainability of agroforestry should be maintained. This study aims to determine the state of sustainability and the key factors ffecting sustainability of agroforestry. The research conducted in Rancah District, Ciamis from April to December 2013. Data is analyzed using RAP-AFS ordinated Regency and prospective analysis. The results showed that some of ecological, economic and social problems potentially threatening the sustainability of agroforestry. Agroforestry in Rancah is less sustainable with sustainability index value of 25.01-50.00 i.e. ecological, economic, social and multidimensional indexes are 32.26, 42.26, 48.59 and 46.20, respectively. The key factors that must be considered for the sustainability of agroforestry are: extension role, the availability of agroforestry technology package, government role and farmer groups existence. Therefore, it is recommended national and regional goverments prioritize the management of the key factors in policy that development of sustainable agroforestry